2016
DOI: 10.1186/s12889-016-2983-3
|View full text |Cite
|
Sign up to set email alerts
|

Decline in physical activity during adolescence is not associated with changes in mental health

Abstract: BackgroundThe majority of studies investigating associations between physical activity and mental health in adolescents have been cross-sectional in design. Potential associations between physical activity and mental health may be better examined longitudinally as physical activity levels tend to decrease in adolescence. Few studies have investigated these associations longitudinally in adolescents and none by measuring physical activity objectively.MethodsA total of 158 Dutch adolescents (mean age 13.6 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
(75 reference statements)
5
20
1
Order By: Relevance
“…We also observed that lower rates of physical activity with a coach was associated with internalizing disorders but this association appeared not to be statistically significant when confounders were considered (Table 3 ). In contrast, several other prospective studies observed no association between physical activity and later depressive symptoms [ 24 26 , 44 ].…”
Section: Discussionmentioning
confidence: 82%
“…We also observed that lower rates of physical activity with a coach was associated with internalizing disorders but this association appeared not to be statistically significant when confounders were considered (Table 3 ). In contrast, several other prospective studies observed no association between physical activity and later depressive symptoms [ 24 26 , 44 ].…”
Section: Discussionmentioning
confidence: 82%
“…Depressive symptoms —The outcome variable was self-reported depressive symptoms measured by the Chinese version of the Center for Epidemiologic Studies Depression (CES-D) Scale [ 22 ], which is widely used in healthy adults and adolescents [ 23 , 24 , 25 ]. The 20-item CES-D Scale measures the levels of depressive symptoms experienced in the past week.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of insufficient and declining levels of physical activity among adolescents [1,2] and inadequate physical fitness [3,4], the high cognitive and emotional load of adolescents in schools is negatively associated with their mental health (MH) [5]. Although some studies have not confirmed the association between physical activity (PA) decline and changes in MH in adolescents, this does not undermine the importance of studying these associations [6]. e prevalence of mental disorders in 12-to 17-year-olds in the USA has been increasing [7,8], as is the case in Europe [9] and other countries [10].…”
Section: Introductionmentioning
confidence: 99%